The regulation of proteins14-3-3 and the hippo pathway affect the adipogenesis or 3T3-L1 - del Veliz, Samanta (2019)
Many transcription factors act sequentially to activate adipocyte differentiation. Multiple signal transduction pathways govern the adipocyte physiology. The Hippo kinase pathway is the main regulator of proliferation and differentiation of stem cells and adipocyte precursor cells. The 14-3-3 protein family, comprised of 7 paralogs in mammals, interacts with components of the Hippo kinase pathway regulating the adipogenic differentiation, although the specificity of these proteins in the process remains elusive. Deciphering the subcellular dynamics of 14-3-3 proteins will be instrumental in the discovery of new targets for the manipulation of stem cell fate decisions or treatment of chronic diseases, such as obesity and type 2 diabetes. In vitro adipocyte differentiation occurs by the addition of an Adipogenic Differentiation Medium (ADM) including Dulbecco's Modified Eagle Medium, 10% Fetal Bovine Serum, synthetic drugs (dexamethasone, IBMX, rosiglitazone) and peptide hormones (insulin). Since these mentioned chemical drugs are not present in physiological environments, it would be important to achieve a correct activated adipogenic program using fewer drugs and with natural origin. We have decided to evaluate the adipogenic potential of glucagon-like peptide 1 (GLP-1) analogs. In contrast to Native GLP-1 action, which is rapidly degraded by circulating Dipeptidyl Peptidase-4, GLP-1 analogs have shown positive effects on glycemic control and body weight due to their greater stability and longer half-life. In this project, experiments were performed on 3T3- L1 preadipocytes. First, the effect of different combinations of drugs for 7 days in adipogenesis was evaluated. Then, we carried out qPCR experiments to measure the gene expression of 14-3-3 and the most important proteins of the Hippo pathway, on days 3 and 7 of differentiation. We have determined that conditions resulting in greater adipogenic differentiation showed higher levels of Hippo pathway proteins and 14-3-3 gamma and beta isoforms on day 7. These effects were especially evident when IBMX was replaced by GLP-1 in the ADM. These results suggest that different inducers (glucocorticoids, thiazolidinediones, incretins), have different abilities for regulating the expression of 14-3-3 and hippo pathway proteins, thus affecting adipogenic differentiation. We are currently focused on elucidating the mechanisms of action of these drugs to have a greater understanding of the events that are necessary for adipogenesis to occur.